Les Contraintes Des Coopératives Dans Le Commerce De La Noix De La Cola À Bouaké (Côte d’Ivoire) - Djibli Vincent Dibi (European Scientific Journal, ESJ, 2018)
This article is an attempt to understand and analyze the difficulties encountered by agricultural cooperatives in the marketing of cola nuts. Despite the considerable capital generated by this sector, many difficulties are hampering the agricultural sector, which results in a sharp decline in the profits of cooperatives and producers. For the members, this is due to the lack or little commitment of the Ivorian State to revitalize this promising sector as is the case with the coffee-cocoa pair. In fact, the fact that foreign traders have direct access to growers in their production areas without going through a central structure, in particular the wholesale marketBouake, weakens domestic traders. Similarly, this situation prevents the Ivorian export circuit of Cola from having a substantial tonnage and allowing the entry of foreign currency into the country. All this contributes to devalue the label of the cola nut produced in Cote d'Ivoire.